The role of anti-TPO as an additional analytical marker in thyroid disease patients in Erbil City - Shawkat Kawther, Ronia; Tahir Lak, Rebaz; Mohammed Zaki Abdullah , Sahar (Diyala Journal of Medicine, 2022)
Background: There is a connection among anti-TPO and anti-TG antibodies and levels of thyroid hormone and both alone or in grouping have been utilized to expect perfection of hypo or hyperthyroidism. Objective: Both alone or in grouping have been utilized to expect perfection of hypo or hyperthyroidism. Patients and Methods: This is a cross-sectional study achieved in the laboratories of Rizgary Teaching Hospital and Erbil Teaching Hospital in Erbil, Iraq, within the period of May 2020 to April 2021. The study included 66 patients, both males and females included. These patients had clinical indications and were suspected of having a sort of thyroiditis. Anti-TPO electrochemiluminescence immunoassay analysis has been included by the analysts in conjunction with conventional markers immunoassay of thyroid TSH, T3, and Free T4 trusting that this would help in lessening morbidity and related wellbeing concerns. Results: There was an increase in the level of anti-TSH antibodies in the hyperthyroidism group (60.6%) which was more than in those with hypothyroidism (36.4%), significant association exist (P≤0.049). Moreover, the level of Anti-TPO Abs was higher among hypothyroidism patients (63.6%) than among hyperthyroidism cases (33.3%), this association was statistically significant (P≤0.014). Conclusion: Demonstrating the clinical importance of this antibody and the benefit of adding anti-TPO, in combination with TSH and FT4. Addition of one test could potentially save expenditure on long-term diseases such as overt thyroid disease and its attended morbidities.